DETERMINAN KEPUTUSAN PETANI KOPI MENJUAL KE TENGKULAK DI DESA SINAR MARGA KECAMATAN MEKAKAU ILIR KABUPATEN OKU SELATAN - Lastinawati, Endang (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
Coffee is a plantation commodity that has a high selling value. However, sometimes farmers do not enjoy the prices prevailing in the market, due to the marketing mechanism that must go through several institutions with a fairly long chain, which affects farmers income. This study aims to calculate the income of coffee farming businesses and analyze the factors that influence farmers to sell coffee to middlemen. The study was conducted in Sinar Marga Village, Mekakau Ilir District, South OKU Regency, using a survey method. The sample of this study was taken by disproportioned simple random sampling, namely 15 farmers who sell to middlemen, and 15 farmers who do not sell to middlemen, so that the total sample is 30 farmers, from a total of 300 coffee farmers in the study location. The objectives of the study were analyzed using the income formula and logistic regression method. The results showed that the average income of farmers who sell coffee to middlemen was IDR 20,482,535.00/ha/year. Meanwhile, the income of farmers who do not sell coffee to middlemen is Rp 19,496,968.00/ha/year. Factors that influence farmers to sell coffee to middlemen are capital loans, distance to the market, selling price, and production costs.